Influence of zinc concentration on band gap and sub-band gap absorption on ZnO nanocrystalline thin films sol-gel grown - Munirah, -; Khan, Z.R.; Aziz, A.; Khan, M.S.; Khandaker, Mayeen Uddin (De Gruyter Open, 2017)
ZnO thin films were fabricated on quartz substrates at different zinc acetate molar concentrations using sol-gel spin coating method. The samples were characterized using X-ray diffraction, field emission scanning electron microscope, UV-Vis spectroscopy, FT-IR spectroscopy and photoluminescence spectroscopy. Sub-band gap absorption of ZnO thin films in the forbidden energy region was carried out using highly sensitive photothermal deflection spectroscopy (PDS). The absorption coefficients of ZnO thin films increased in the range of 1.5 eV to 3.0 eV, upon increasing zinc concentration. The optical band gaps were evaluated using Tauc's plots and found to be in the range of 3.31 eV to 3.18 eV. They showed the red shift in the band edge on increase in zinc concentration. The PL spectra of ZnO thin films revealed the characteristic band edge emission centered at the 396 nm along with green emission centered at the 521 nm.